The Rapid Emergence of Tigecycline Resistance in blaKPC–2 Harboring Klebsiella pneumoniae, as Mediated in Vivo by Mutation in tetA During Tigecycline Treatment - Du, Xiaoxing; He, Fang; Shi, Qiucheng; Zhao, Feng; Xu, Juan; Fu, Ying; Yu, Yunsong (Frontiers in Microbiology, 2018)
Tigecycline is one of the last resort treatments for carbapenem-resistant Klebsiella pneumoniae (CRKP) infections. Tigecycline resistance often occurs during the clinical treatment of CRKP, yet its mechanism has still not been clearly elucidated. This study presents an analysis of a tigecycline resistance mechanism that developed in clinical isolates from a 56-year-old female patient infected with CRKP during tigecycline treatment. Consecutive clonal consistent K. pneumoniae isolates were obtained during tigecycline treatment. Whole genome sequencing (WGS) of the isolates was performed, and putative single nucleotide polymorphisms (SNPs), insertion and deletion mutations were analysed in susceptible and resistant isolates. The identified gene of interest was examined through experiments involving transformations and conjugations. Four isolates, two of which were susceptible and two resistant, were collected from the patient. All of the isolates belonged to Sequence Type 11 (ST11) and were classified as extensively drug resistant (XDR). One amino acid substitution S251A in TetA was identified in the tigecycline resistant isolates. Subsequent transformation experiments confirmed the contribution of the TetA variant (S251A) to tigecycline resistance. The transfer capacity of tigecycline resistance via this mutation was confirmed by conjugation experiments. Using southern blot hybridization and PCR assays, we further proved that the tetA gene was located on a transferable plasmid of ca. 65 kb in an E. coli EC600 transconjugant. Our results provide direct in vivo evidence that evolution in the tetA gene can lead to tigecycline treatment failure in CRKP clinical strains that carry tetA. Moreover, the transfer capacity of tigecycline resistance mediated by mutated tetA is a threat.